Adios, pajarito, adios! - Allan, Nicholas (Caracas, Venezuela : Ediciones Ekare, 1997)
A hermit, happily alone on an island, rejects the friendship of an uninvited bird and banishes him, only to miss him, while the bird has flown away to find his own friends, the animals and people from the Noah's ark.
Translation of: The bird.
Keywords: Birds -- Fiction